PENGARUH KINERJA DAN KUALITAS PELAYANAN TERHADAP CITRA PERUSAHAAN PADA BRI CABANG GARUT - Itto Turyandi (KarismaPro, 2020)
BRI branch Garut is a company engaged in services are always required to provide quality service to its customers. Dimensions of service quality such as: physical evidence, reliability, responsiveness, assurance, and empathy should always be implemented optimally in order to create a positive corporate image in the eyes of the customer as a positive corporate image will have an impact on customer perception of the BRI branch Garut.The purpose of this study was to determine the performance quality of service at the BRI branch Garut, to determine the image of the company at the BRI Branch Garut and to determine how much influence the performance quality of service to the company's image on the Index.php BRI Branch. The method used in this research is descriptive and verification methods. Descriptive study conducted to obtain an overview of the performance of service quality and corporate image. While the verification study conducted to determine the relationship between variables through statistical calculations. Data obtained by the preparation of thesis literature study, interviews, observation and questionnaires and use formulas to analyze data and Spearman rank assisted by SPSS 11.0 for windows. The survey sampled 100 respondents with an error level of 10%. Based on the results of this research is that the correlation between the performance levels of service quality relationship with the company image shows both the strength and direction of variables. influence the performance of quality of service to the company's image by 60.84%, while the remaining 39.16% is influenced by other factors, such as customer satisfaction and customer loyalty. That is, the better the performance of quality of service provided, the better the image of the company at the BRI branch Garut